Emerging From the COVID-19 Crisis With a Stronger Health Care Workforce. (December 2020) - Dow, Alan W.; DiPiro, Joseph T.; Giddens, Jean; Buckley, Peter; Santen, Sally A.
Abstract : The COVID-19 pandemic has highlighted the limitations of the current health care workforce. As health care workers across the globe have been overwhelmed by the crisis, oversight entities and training programs have sought to loosen regulations to support ongoing care. Notably, however, workforce challenges preceded the current crisis. Now may be the time to address these underlying workforce challenges and emerge from the COVID-19 pandemic with a stronger health care workforce. Building upon historical exemplars in the context of the current crisis, the authors of this Perspective provide a roadmap to rapidly and safely increase the workforce for COVID-19 and beyond. The authors recommend the following: (1) a comprehensive approach to guide health care workforce development, (2) streamlining transitions to the next level of practice, (3) reciprocity among state licensing boards or national licensure, (4) payment reform to support a strengthened health care workforce, and (5) efforts by employers to ensure the ongoing safety and competence of the bolstered workforce. These steps require urgent collaboration among stakeholders commensurate with the acuity of the pandemic. Implemented together, these actions could address not only the novel challenges presented by COVID-19 but also the underlying inadequacies of the health care workforce that must be remedied to create a healthier society.